2013
DOI: 10.1111/jvh.12159
|View full text |Cite
|
Sign up to set email alerts
|

HLADQ polymorphisms with HBV infection: different outcomes upon infection and prognosis to lamivudine therapy

Abstract: Two recent genome-wide studies showed that the single-nucleotide polymorphisms in the HLA-DQ region (rs2856718 and rs9275572) were associated with chronic hepatitis B virus infection and chronic hepatitis C virus-associated hepatocellular carcinoma in Japanese patients. We tested the effects of the two single-nucleotide polymorphisms for all major HBV outcomes and lamivudine treatment in Han Chinese. A total of 1649 samples were enrolled, and peripheral blood samples were collected in this study. The single-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
(26 reference statements)
3
23
0
1
Order By: Relevance
“…The present study revealed that HBeAg‐negative patients with rs2856718 genotype AG + GG developed HCC less frequently than those with genotype AA (Table ). This result corresponds to the previously reported association between rs2856718 and HCC development, although there have also been three studies that did not find any such association . This discordance of results may be attributed to the differences in the disease phases and genetic characters of the population studied.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study revealed that HBeAg‐negative patients with rs2856718 genotype AG + GG developed HCC less frequently than those with genotype AA (Table ). This result corresponds to the previously reported association between rs2856718 and HCC development, although there have also been three studies that did not find any such association . This discordance of results may be attributed to the differences in the disease phases and genetic characters of the population studied.…”
Section: Discussionsupporting
confidence: 87%
“…reported that the G allele of rs2856718 and the A allele of rs7453920 were associated with HBV clearance and that the G allele of rs2856718 decreased host HCC risk . Two further studies confirmed the association between rs2856718 and HBV clearance . One study confirmed the association between rs2856718 and HCC development, but three other studies did not find any association .…”
Section: Introductionmentioning
confidence: 98%
“…Analyses of Hu et al showed that HLA-DQ rs2856718 significantly decreased host HCC risk, whereas two SNPs (rs2856718 and rs7453920) were associated with HBV clearance [8, 11]. Zhang et al confirmed that HLA-DQ rs2856718G is strongly associated with decreased risk of chronic HBV infection and natural clearance [13]. Meanwhile, several other studies conducted on other populations have investigated the role of HLA-DQ polymorphisms (rs2856718 and rs7453920) on the development of persistent chronic HBV infection or its natural clearance [7, 1418].…”
Section: Discussionmentioning
confidence: 99%
“…It is related to a complex gene regulation and control system in the human body (12). Since the 1990s, research on (13) HLA alleles in the human body (14) and HLA related diseases (15,16) in chronic myeloid leukemia has shown that the frequencies of HLA-A32, B27, B45 and B44 were significantly higher than those in the control group (17). The HLA-A32 gene frequency was lower compared to the control group, and with further study of the HLA-II genotype, it was found that HLA-II genotype in the human body is not only involved in an external immune response of the body, but also has an important role in the promotion of the maturation of lymphocytes and other immune cells in vivo (18).…”
Section: Discussionmentioning
confidence: 99%